The Moderating Effect of Government Policy on the Relationship Between Financial Literacy and the Use of Financial Technology by MSMEs - Pranoto, Adam Joyo (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Low financial literacy among MSMEs in Indonesia is a significant problem, as it hinders the adoption of financial technology (fintech) that could improve their efficiency and competitiveness. This study aims to analyze how government policies moderate the relationship between financial literacy and the use of financial technology by MSMEs. This research uses a qualitative approach with a literature study method. Data was collected from various secondary sources, including scientific journals, books, government reports, and other relevant publications. The research process involved identifying relevant literature, content analysis to understand the interaction between financial literacy, government policies, and fintech usage, and synthesis of findings to draw a comprehensive conclusion. The results show that financial literacy has a positive influence on the use of fintech by MSMEs. Government policies act as a significant moderating factor in the relationship between financial literacy and fintech usage. The conclusion of this study emphasizes the importance of government policies in improving financial literacy and encouraging the use of financial technology by MSMEs. It is suggested that the government should continue to develop and implement policies that support financial literacy and fintech adoption. In addition, collaboration between the government, financial institutions, and technology providers needs to be strengthened to create a conducive ecosystem for the growth of MSMEs.